2005
DOI: 10.1177/229255030501300403
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reporting Return to Work in Studies Comparing Open with Endoscopic Carpal Tunnel Release: A Review of Randomized Controlled Trials

Abstract: BACKGROUND:In studies comparing open with endoscopic carpal tunnel release, return to work (RTW) is often cited as a primary outcome. OBJECTIVE: The present study assessed the reporting of RTW and evaluated its usefulness in studies comparing these two methods of carpal tunnel release. METHODS: A computerized search was conducted to find randomized controlled trials that compared open with endoscopic carpal tunnel release, with RTW as an outcome measure. The factors that were compared across the studies includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(106 reference statements)
1
8
0
Order By: Relevance
“…32,33 In addition, whereas measures such as grip strength and return to work status ideally reflect function and recovery, return to work is an imperfect measure of recovery because it is highly dependent on factors unrelated to nerve recovery itself, such as patient motivation, occupation, and surgeon expectations. 6,7 Finally, the follow-up of 6 weeks after surgery is short; however, Atroshi et al 1 showed that improvement in symptoms and functional status can be expected in the first 6 weeks, as supported by the statistically significant differences in CTSAQ scores observed here.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…32,33 In addition, whereas measures such as grip strength and return to work status ideally reflect function and recovery, return to work is an imperfect measure of recovery because it is highly dependent on factors unrelated to nerve recovery itself, such as patient motivation, occupation, and surgeon expectations. 6,7 Finally, the follow-up of 6 weeks after surgery is short; however, Atroshi et al 1 showed that improvement in symptoms and functional status can be expected in the first 6 weeks, as supported by the statistically significant differences in CTSAQ scores observed here.…”
Section: Discussionsupporting
confidence: 70%
“…21,30,31 Although evidence has been mixed, ECTR demonstrated functionally significant improvement in grip strength and faster return to work (8 days sooner, on average) in various reports. 6,7 Patients who underwent ECTR had a decrease in median nerve CSA (e1.9 mm 2 ), in contrast to an increase in CSA (þ0.6 mm 2 ) in the MOCTR group. Both groups demonstrated a statistical improvement in both SSS and FSS; however, the improvement in FSS in the MOCTR group lacked a clinically important change when using a change of 1.04 as a threshold.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, conventional open carpal tunnel release surgery can be associated with increased surgical trauma that results in longer postoperative recovery times. A further postoperative complication of conventional release surgery is the formation of scar tissue on the palm of the hand and scar tenderness that can be associated with the development of a neuroma in the palmar cutaneous nerve branch, which can affect the postoperative quality of life [9].…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistencies in the definition and measurement of time to RTW in CTR settings have been previously discussed (73). The authors called for standardized assessment of RTW, measured in days, and including information on type of work, insurance status and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%